Analysis of Elastohydrodynamic Lubrication Characteristic of the Roller Enveloping Hourglass Worm Drive - Taoran Zhang; Lingyu Li (Jixie chuandong)
To study the elastohydrodynamic lubrication（EHL） characteristic of the roller enveloping hourglass worm drive， the line contact isothermal mathematical model is established based on the research of meshing theory of the roller enveloping hourglass worm drive and the theory of EHL. The elastohydrodynamic lubrication of drive pair is solved by using direct iterative method， the curves of oil film pressure and thickness of this drive pair are obtained. At the same time， the elastohydrodynamic lubrication characteristic of dedendum circle， reference circle and addendum circle of drive pair are analyzed. The influence of orifice coefficient and roller radius to EHL characteristics on this worm drive are analyzed at last. The example analysis results indicated that this transmission has better EHL characteristics， the EHL performance of the drive can be improved by properly increasing orifice coefficient and roller radius.